Pengaruh Pengaruh Lingkungan Kerja Dan Penghasilan Terhadap Motivasi Dan Dampaknya Pada Produktivitas Kerja Karyawan (Studi Kasus Pada UMKM di Kecamatan Gondanglegi Kabupaten Malang) - Fayi’ Hilmy Musyafiq; Ronny Malavia Mardani; Andi Normaladewi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine The Influence of the Work Environment and Income on Employee Motivation and the Impact on Work Productivity (In UMKM in Gondanglegi District, Malang Regency). This research is a type of quantitative research. The method used is multiple linear regression. The sampling technique uses the formula from Malhotra with the calculation of the number of indicators multiplied by 5 (18x5) the calculation results are 90 samples. To solve the problems in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that significantly. Effect of Work Environment (X1), Income (X2), significant positive effect on Employee Motivation (Y1), and Work Productivity (Y2) in MSMEs (Micro, Small and Medium Units) in Gondanglegi District, Malang Regency. Keywords: The Effect Of Work Environment And Income On Employee Motivation And Its Impact On Work Productivity.